Dehidrasi Bioetanol Hasil Fermentasi Nira Nipah Dengan Modifikasi Bentonit Dan Variasi Rasio Adsorben - Utami, Syelvia Putri; Hidayat, Wahyu; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Energy need is continously supplied by fossil fuels source The existence of environmental issues and facts about the limited resources of fossil fuels results in an energy crisis that will cause disruption of the world economy. The energy crisis has stimulated efforts to the use and development of renewable fuels and benign envinronmentally. Another method is by using bioethanol derived from nypa sap as an alternative energy source that is renewable. This study aimed to obtain data correlation ratio between the adsorbent and bioethanol against purity ethanol by distillation-adsorption process, and then obtain data on the effect of modification of bentonite activation without the addition of starch and with the addition of starch to bioethanol purity by distillation-adsorption process, and characterize the physical properties of ethanol. This research was conducted in three phases: bioethanol fermentation, modified bentonite and bentonite purification by distillation-adsorption process. For distillation-adsorption, they were conducted at 78oC by using 200 mesh bentonite .This study focused on ratio bentonite and starch addition. They were 1:2, 1:3, 1:4 and 0%, 35%,40%, 45% respectively. The most effective process in bioethanol purification was distillation-adsorption employed 45% starch addition by using 1:2 activated bentonite. It raised concentration bioethanol 95% to 99.7% v/v.Keywords : Bentonite, bioethanol, destillation-adsorption, fermentation, nypa sap, starch